2016
DOI: 10.1007/s00784-016-1855-7
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of lower canine retraction and loss of anchorage between conventional and self-ligating brackets: a single-center randomized split-mouth controlled trial

Abstract: Using self-ligating brackets to retract lower canines will not increase the velocity of tooth movement, does not increase anchorage, and does not decrease tipping.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 41 publications
(44 reference statements)
1
1
0
3
Order By: Relevance
“…We cannot find enough data dealing with the acceleration rate of lower canine movements. However, our results could be compared to the results found by Aslan et al (39) who reported a lower canine retraction rate ranging from 0.88 to 0.93 mm/month and Monini et al (40) who found the rate of canine retraction in lower canine was 0.54 mm/month for SLB and 0.60 mm/month for CB.…”
Section: Table (2) Comparison Between the Four Studied Groups Accordi...supporting
confidence: 62%
“…We cannot find enough data dealing with the acceleration rate of lower canine movements. However, our results could be compared to the results found by Aslan et al (39) who reported a lower canine retraction rate ranging from 0.88 to 0.93 mm/month and Monini et al (40) who found the rate of canine retraction in lower canine was 0.54 mm/month for SLB and 0.60 mm/month for CB.…”
Section: Table (2) Comparison Between the Four Studied Groups Accordi...supporting
confidence: 62%
“…En cuanto a las etapas del tratamiento ortodóncico, en la alineación y nivelación no existirían diferencias significativas entre los distintos tipos de aparatos fijos (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33) . Al evaluar la pérdida de anclaje no se encontró evidencia significativa que muestre alguna diferencia entre los distintos tipos de brackets, lo mismo al compararlos en el cierre de espacios (24,(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46) . En relación con la expresión de torque, los brackets convencionales tienen mejores resultados al compararlos con los brackets de autoligado (16,47,48) y por último, al analizar la expansión transversal no existe evidencia que muestre una superioridad de brackets de autoligado comparado con brackets convencionales (33,46,(49)(50)(51)(52)(53)(54)(55)(56)(57) .…”
Section: Discussionunclassified
“…Se comparó la pérdida de anclaje entre brackets convencionales y de autoligado pasivos, concluyendo que no existe diferencia en la pérdida de anclaje entre ambos (34) . Similares resultados se obtuvieron en varios estudios al comparar brackets de autoligado con brackets convencionales (35)(36)(37)(38)(39) . Las revisiones sistemáticas en relación con este aspecto concluyen que, tanto los brackets convencionales como los de autoligado, mostraron la misma pérdida de anclaje (40) y que no se encontró evidencia que sugiriera que existe una diferencia significativa entre brackets convencionales y autoligados (41) .…”
Section: Pérdida De Anclajeunclassified
See 1 more Smart Citation
“…Monini et al . [ 36 37 ] employed a vertical reference line perpendicular to the occlusal plane on both sides of oblique lateral cephalometric radiographs. The canine movement was indicated by the horizontal distance between the vertical reference line and the canine cusp point.…”
Section: Methods Of Measuring Distal Canine Movementmentioning
confidence: 99%